Preparation method of niobium-titanium-oxygen material

By using niobium titanium oxide materials as niobium ammonium oxalate as niobium ammonium oxalate as niobium source and combining low melting point doping elements to construct porous nanostructures, the problem of low conductivity of the material is solved, and electrochemical performance and high-current charging and discharging capacity are improved. , especially suitable for fast charging and discharging fields.

CN119118197APending Publication Date: 2024-12-13RES INST OF CHEM DEFENSE PLA ACAD OF MILITARY SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410992701.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-23
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The electronic conductivity and ionic conductivity of niobium titanium oxide materials are low, which affects its electrochemical properties.

Method used

Using niobium oxalate or ammonium oxalate as niobium oxalate source, the porous nanostructure framework is constructed through high-temperature thermal decomposition, and combining the first doping element and the second doping element at low melting point to reduce the heat treatment temperature and particle size, increase the concentration of structural defects, and improve the The ionic conductivity of the material.

Benefits of technology

The morphology control and doping of bulk elements of niobium titanium oxide materials have been realized, and the electrochemical performance of the material has been improved, especially in high current charging and discharging and low temperature environments. The discharge specific capacity reaches 190mAh/g, and the capacity of 300 cycles is increased. The retention rate is close to 100%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119118197A_ABST
    Figure CN119118197A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of battery raw materials, and particularly relates to a preparation method of a niobium-titanium-oxygen material. According to the method, decomposable niobium salt is adopted as a niobium source and is subjected to high-temperature thermal decomposition to construct a niobium-titanium-oxygen material porous nanostructure framework, and the particle size of the niobium-titanium-oxygen material is effectively reduced; the low-melting-point first doping element is used for reducing the heat treatment temperature of the niobium-titanium-oxygen material, material crystal growth at high temperature is avoided, and the particle size of the niobium-titanium-oxygen material is reduced; the first doping element and the second doping element act together to increase the defect concentration in the niobium-titanium-oxygen material structure and improve the intrinsic ion conductivity of the material, so that the electrochemical performance of the niobium-titanium-oxygen material is improved. The niobium-titanium-oxygen material prepared by the method has the advantages of uniform particle size distribution, excellent large-current charge-discharge capacity and low-temperature performance, charge-discharge and discharge specific capacity of 190mAh / g at 10C, capacity retention rate of 300 cycles close to 100%, simple preparation process and wide application prospect, and is particularly suitable for the field of large-current rapid charge-discharge.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of battery raw materials, and specifically relates to a method for preparing a niobium-titanium oxide material. Background Art

[0002] Lithium-ion batteries have the advantages of high energy density, high operating voltage, high safety performance, wide operating temperature range and long cycle life. They have been widely used in portable electronic products, electric vehicles, energy storage power stations and other fields, and are the current mainstream development direction of rechargeable batteries.

[0003] The main components of lithium-ion batteries include positive and negative electrode materials, electrolytes and diaphragm materials. As a key material, the choice of negative electrode material directly determines the performance of the battery.

[0004] Niobium titanium oxide materials in Li + It has excellent structural stability during the insertion / extraction process and excellent cycle stability; during the electrochemical reaction, there are three redox pairs (Nb 5+ / Nb 4+ , Nb 4+ / Nb 3+ , Ti 4+ / Ti 3+ ), the theoretical specific capacity is 388 mAh g -1 , has a high energy density; and it has a relatively high working potential (~1.6V vs Li + / Li), which can avoid the formation of lithium dendrites and make the battery have good safety. These advantages make niobium titanium oxide materials promising to become the negative electrode material of the next generation of lithium-ion batteries.

[0005] Despite this, niobium titanium oxide materials also have some disadvantages when used as negative electrode materials for lithium-ion batteries. For example, their energy band gap is wide, and their electronic and ionic conductivity are poor. Therefore, it has become an important research direction to modify niobium titanium oxide materials, improve the electrochemical kinetics of materials, and improve electronic and ionic conductivity. At present, the main modifications of niobium titanium oxide materials are: morphology control, surface modification, and bulk element doping. Morphology control mainly reduces the particle size and shortens the lithium ion deintercalation path. Surface modification is mainly carbon coating. The carbon coating layer can not only increase the electronic conductivity of niobium titanium oxide materials, but also reduce the agglomeration of niobium titanium oxide and form oxygen vacancies, thereby further improving the ionic conductivity of niobium titanium oxide materials. However, the presence of the carbon coating layer causes the valence state of Nb to change at high temperatures, resulting in an unstable niobium titanium oxide structure, which is not conducive to the long cycle of the battery. Bulk element doping is to partially replace Ti or Nb, increase the defect concentration in the niobium titanium oxide structure, and thus improve the intrinsic ionic conductivity.

[0006] The present invention combines morphology control with bulk element doping, utilizes thermal decomposition of a niobium source to construct a porous nanostructure skeleton of a niobium titanium oxide material, utilizes a first doping element to reduce the heat treatment temperature of the niobium titanium oxide material, and the first doping element and the second doping element synergistically increase the defect concentration in the structure of the niobium titanium oxide material, thereby improving the intrinsic ionic conductivity of the material. Summary of the invention

[0007] The purpose of the present invention is to solve the problem of low electronic conductivity and ionic conductivity of niobium titanium oxide materials, and to provide a method for preparing niobium titanium oxide materials. Niobium oxalate or ammonium niobium oxalate is used as a niobium source, and its high-temperature thermal decomposition constructs a porous nanostructure skeleton of the niobium titanium oxide material; a low-melting-point first doping element is used to reduce the heat treatment temperature of the niobium titanium oxide material and reduce the particle size of the niobium titanium oxide material; the first doping element and the second doping element work together to increase the defect concentration in the structure of the niobium titanium oxide material, improve the intrinsic ionic conductivity of the material, and thus improve the electrochemical performance of the niobium titanium oxide material.

[0008] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0009] In a first aspect, the present invention provides a method for preparing a niobium-titanium oxide material, comprising the following steps:

[0010] Step 1: Preparation of raw material mixture

[0011] The niobium source, titanium dioxide, the first dopant and the second dopant are uniformly mixed in proportion to obtain a raw material mixture;

[0012] The niobium source is one of niobium oxalate and ammonium niobium oxalate or a mixture of the two;

[0013] The first dopant is one or a mixture of two or more of lithium carbonate, lithium acetate, lithium hydroxide, sodium carbonate, sodium acetate, sodium hydroxide, potassium carbonate, potassium acetate or potassium hydroxide;

[0014] The second dopant is at least one of an oxide containing zirconium, tungsten, magnesium, tantalum, chromium, vanadium, aluminum, manganese, iron, cobalt, nickel, copper, zinc, tin or yttrium;

[0015] The molar ratio of the niobium source, titanium dioxide, the first dopant and the second dopant is 2-4:1:0.001-0.1:0.001-0.1;

[0016] Step 2: Preparation of Precursor

[0017] The prepared raw material mixture is heat-treated at 400-800° C. for 1-10 hours in an air atmosphere to obtain a precursor;

[0018] Step 3: Preparation of niobium titanium oxide material

[0019] The prepared precursor is heat treated at 800-1300° C. for 3-20 hours in an air atmosphere to obtain a niobium-titanium oxide material.

[0020] Preferably, the particle size of the titanium dioxide is 10 to 100 nm, and the particle size of the second dopant is 10 to 100 nm.

[0021] Preferably, in step 2 and step 3, the raw material mixture and the precursor are placed in a sintering furnace for heat treatment.

[0022] Preferably, in the prepared niobium titanium oxide material, the first dopant and the second dopant are uniformly distributed in the lattice of the niobium titanium oxide material and participate in the formation of the niobium titanium oxide material.

[0023] Preferably, the particle size of the prepared niobium titanium oxide material is 0.1-2 μm.

[0024] In a second aspect, the present invention provides a niobium-titanium oxide material prepared by the method described in the first aspect.

[0025] In a third aspect, the present invention provides an application of the niobium titanium oxide material described in the second aspect, for use as a battery pole piece.

[0026] Preferably, the battery is a lithium ion battery or a sodium ion battery.

[0027] Furthermore, the battery electrode is a negative electrode.

[0028] In a fourth aspect, the present invention provides a battery using a niobium titanium oxide material as a pole piece, wherein the niobium titanium oxide material described in the second aspect is a negative pole piece, a polypropylene microporous membrane is used as a separator, a metal lithium sheet is used as a counter pole piece, and the electrolyte is a wide temperature range electrolyte.

[0029] Beneficial effects of the present invention: This method realizes the combination of morphology control and bulk element doping of niobium titanium oxide materials, and has the following advantages:

[0030] 1. Using niobium oxalate or ammonium niobium oxalate as the niobium source, its high-temperature thermal decomposition constructs a porous nanostructure skeleton of niobium titanium oxide material, effectively reducing the particle size of niobium titanium oxide material;

[0031] 2. Using low melting point lithium, sodium or potassium as the first doping element can reduce the heat treatment temperature of niobium titanium oxide materials, avoid the growth of material crystals at high temperatures, and reduce the particle size of niobium titanium oxide materials;

[0032] 3. The first doping element and the second doping element work together to increase the defect concentration in the structure of the niobium titanium oxide material, thereby improving the intrinsic ionic conductivity of the material and thereby improving the high current charge and discharge performance of the niobium titanium oxide material;

[0033] 4. The niobium titanium oxide material prepared by this method has uniform particle size distribution, excellent large current charge and discharge capability and low temperature performance. When charged and discharged at 10C, the discharge specific capacity reaches 190mAh / g, and the capacity retention rate after 300 cycles is close to 100%. It has broad application prospects and is particularly suitable for the field of large current rapid charge and discharge. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 SEM image of niobium titanium oxide material (50μm)

[0035] Figure 2 SEM image of niobium titanium oxide material (5μm)

[0036] Figure 3 0.2C charge and discharge curve of niobium titanium oxide material at -40℃

[0037] In the figure: the vertical axis is voltage, unit V; the horizontal axis is specific capacity, unit mAh / g

[0038] Figure 4 300 charge and discharge cycle curves of niobium titanium oxide material at room temperature and 10C

[0039] In the figure: the ordinate is the discharge capacity, in mAh / g; the abscissa is the number of cycles, in times. DETAILED DESCRIPTION

[0040] The present invention will be further described below in conjunction with the accompanying drawings and examples.

[0041] Example 1

[0042] The niobium titanium oxide material provided in Example 1 of the present invention comprises the following specific steps:

[0043] Step 1: Preparation of raw material mixture

[0044] The niobium oxalate, titanium dioxide, lithium acetate and zirconium dioxide are uniformly mixed in a molar ratio of 2.2:1:0.02:0.02 to obtain a raw material mixture;

[0045] Among them, the particle size of titanium dioxide is 20nm, and the particle size of zirconium dioxide is 20nm;

[0046] Step 2: Preparation of Precursor

[0047] The prepared raw material mixture is placed in a sintering furnace and heat treated at 600°C for 3 hours in an air atmosphere to obtain a precursor;

[0048] Step 3: Preparation of niobium titanium oxide material

[0049] The prepared precursor was placed in a sintering furnace and heat treated at 1100°C for 10 hours in an air atmosphere to obtain a niobium-titanium oxide material.

[0050] The obtained niobium titanium oxide material has a uniform particle size of about 1 μm. Figure 1 and Figure 2 shown.

[0051] Niobium oxalate or ammonium niobium oxalate is used as the niobium source, and its high-temperature thermal decomposition constructs a porous nanostructure skeleton of the niobium titanium oxide material, effectively reducing the particle size of the niobium titanium oxide material; low-melting-point lithium, sodium or potassium is used as the first doping element to reduce the heat treatment temperature of the niobium titanium oxide material, avoid the crystal growth of the material at high temperature, and reduce the particle size of the niobium titanium oxide material.

[0052] Example 2

[0053] The niobium titanium oxide material provided in Example 2 of the present invention comprises the following specific steps:

[0054] Step 1: Preparation of raw material mixture

[0055] ammonium niobium oxalate, titanium dioxide, sodium acetate and vanadium oxide are uniformly mixed in a molar ratio of 2.1:1:0.03:0.03 to obtain a raw material mixture;

[0056] Among them, the particle size of titanium dioxide is 10nm, and the particle size of vanadium oxide is 50nm;

[0057] Step 2: Preparation of Precursor

[0058] The prepared raw material mixture is placed in a sintering furnace and heat treated at 650°C for 2 hours in an air atmosphere to obtain a precursor;

[0059] Step 3: Preparation of niobium titanium oxide material

[0060] The prepared precursor was placed in a sintering furnace and heat treated at 1200° C. for 5 hours in an air atmosphere to obtain the niobium titanium oxide material.

[0061] Test Case

[0062] The niobium titanium oxide negative electrode material prepared in Example 1 of the present invention was made into an electrode sheet, a Celgard 2400 polypropylene microporous membrane was used as a separator, a metal lithium sheet was used as a counter electrode sheet, a wide temperature range electrolyte was added, and a button battery of model CR2025 was assembled in an argon atmosphere glove box. The assembled button battery was placed in a low temperature box and subjected to a 0.2C constant current charge and discharge test at -40°C. The charge and discharge curves are shown in FIG. Figure 3 As shown in the figure, the discharge capacity at -40°C reaches 288mAh / g, and the charge capacity is 275mAh / g, showing excellent low-temperature charge and discharge performance. The assembled button battery was subjected to 10C charge and discharge cycles at room temperature, and the cycle curve is shown in the figure. Figure 4As shown, the capacity retention rate after 300 cycles at 10C is close to 100%, demonstrating excellent high-current charge and discharge performance, and is particularly suitable for the field of high-current fast charge and discharge batteries.

[0063] The wide temperature range electrolyte preparation method is as follows: 4g of polyethylene glycol dimethacrylate, 100g of electrolyte, and 8g of nano lithium lanthanum zirconium oxide powder are allowed to stand at 60°C for 6h; wherein the electrolyte composition is 1.2mol / L lithium hexafluorophosphate+0.2mol / L lithium tetrafluoroborate+0.2mol / L lithium bis(fluorosulfonyl)imide, and the solvent is 20ml of cyclopentane sulfone, 20ml of diethyl sulfone, 30ml of diethyl carbonate, 20ml of ethyl propionate, and 10ml of fluoroethylene carbonate.

[0064] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art may make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.

Claims

1. A method for preparing a niobium-titanium oxide material, characterized in that: The preparation steps are as follows: Step 1: Preparation of raw material mixture The niobium source, titanium dioxide, the first dopant and the second dopant are uniformly mixed in proportion to obtain a raw material mixture; The niobium source is one of niobium oxalate and ammonium niobium oxalate or a mixture of the two; The first dopant is one or a mixture of two or more of lithium carbonate, lithium acetate, lithium hydroxide, sodium carbonate, sodium acetate, sodium hydroxide, potassium carbonate, potassium acetate or potassium hydroxide; The second dopant is at least one of an oxide containing zirconium, tungsten, magnesium, tantalum, chromium, vanadium, aluminum, manganese, iron, cobalt, nickel, copper, zinc, tin or yttrium; The molar ratio of the niobium source, titanium dioxide, the first dopant and the second dopant is 2-4:1:0.001-0.1:0.001-0.1; Step 2: Preparation of Precursor The prepared raw material mixture is heat-treated at 400-800° C. for 1-10 hours in an air atmosphere to obtain a precursor; Step 3: Preparation of niobium titanium oxide material The prepared precursor is heat treated at 800-1300° C. for 3-20 hours in an air atmosphere to obtain a niobium-titanium oxide material.

2. The method for preparing the niobium titanium oxide material according to claim 1, characterized in that: The particle size of the titanium dioxide is 10-100 nm, and the particle size of the second dopant is 10-100 nm.

3. The method for preparing the niobium titanium oxide material according to claim 1, characterized in that: In the step 2 and step 3, the raw material mixture and the precursor are placed in a sintering furnace for heat treatment.

4. The method for preparing the niobium-titanium oxide material according to claim 1, characterized in that: In the prepared niobium titanium oxide material, the first dopant and the second dopant are uniformly distributed in the lattice of the niobium titanium oxide material and participate in the formation of the niobium titanium oxide material.

5. The method for preparing the niobium-titanium oxide material according to claim 1, characterized in that: The particle size of the prepared niobium titanium oxide material is 0.1-2 μm.

6. A niobium-titanium oxide material prepared by the method according to any one of claims 1 to 5.

7. Use of the niobium-titanium oxide material according to claim 6 as a battery pole piece.

8. The use of the niobium titanium oxide material according to claim 6, characterized in that: The battery is a lithium ion battery or a sodium ion battery.

9. The use of the niobium titanium oxide material according to claim 8, characterized in that: The battery pole piece is a negative pole piece.

10. A battery using niobium-titanium oxide material as a pole piece, characterized in that: The niobium titanium oxide material described in claim 6 is used as the negative electrode plate, a polypropylene microporous membrane is used as the diaphragm, a metal lithium sheet is used as the counter electrode plate, and the electrolyte is a wide temperature range electrolyte.